Postgraduate Course “History and Philosophy of Science”: What? How? What for? - E. N. Ivakhnenko (Высшее образование в России)
The article addresses the problem of teaching the course of history and philosophy of science. This course has been taught to graduate students of Russian universities for more than 15 years. But disputes over its content and expediency still do not subside, but only flare up with renewed vigor. Those disputes were in three directions. The author proposes to return to the discussion of the existing problems in each of the areas of criticism of postgraduate discipline. These are: 1) the content of the subject from the standpoint of the coordination of its historical and philosophical parts (What?); 2) pedagogical and methodological support of training (How?); and 3) the ultimate goals of postgraduate training in general (For what?). The questions “how?” and “ what for?” are included in a broader context – the formation of the competence of a future scientist, his readiness to solve complex and non-trivial scientific problems. Reflections outlined in the article are built into the overall picture of post-graduate training in universities that has developed to date. The author sums up his reflections by calling for non-stop communication in a mode of continuous “recursive adjoining”. Such a strategy, in his opinion, remains the most reliable means of highquality promotion of both teaching and training of graduate students in general.